2019
DOI: 10.1016/j.jaci.2018.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Eleven loci with new reproducible genetic associations with allergic disease risk

Abstract: Using a gene-based approach, we identified 11 risk loci for allergic disease that were not reported in previous GWASs. Functional studies that investigate the contribution of the 19 associated genes to the pathophysiology of allergic disease and assess their therapeutic potential are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 60 publications
1
63
0
Order By: Relevance
“…Ferreira et al report eleven loci having new reproducible genetic associations with allergic disease risk [8]. Of these, diminished FOSL2, APOBR and NCF4 RNA expression are significantly associated with increased glioma survival.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ferreira et al report eleven loci having new reproducible genetic associations with allergic disease risk [8]. Of these, diminished FOSL2, APOBR and NCF4 RNA expression are significantly associated with increased glioma survival.…”
Section: Resultsmentioning
confidence: 99%
“…Genetic loci examined were chosen if they were associated with glioma (1p, 19q, TERT, ATRX) or allergy (FOSL2, APOBR and NCF4) [8]. …”
Section: Methodsmentioning
confidence: 99%
“…Another level of complexity is that both mIL‐6R and sIL‐6R also bind the p28 subunit of IL‐27, with the sIL‐6R/p28 complex having antiviral activity . IL‐27 has been implicated in the aetiology of allergic disease, both by functional and genetic association studies . Therefore, a role for IL‐6R inhibition in IL‐27‐dependent allergic responses should also be considered in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…89 IL-27 has been implicated in the aetiology of allergic disease, both by functional 90 and genetic association studies. 91,92 Therefore, a role for IL-6R inhibition in IL-27-dependent allergic responses should also be considered in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…So far, 31 risk loci for AD have been identified, and most susceptibility loci are related to (auto-)immune regulation, in particular, innate signaling and T-cell activation [47]. Moreover, genome-wide association studies have revealed that asthma, hay fever, and eczema share 136 risk variants in 99 loci that dysregulate the expression of immune-related genes [48]. …”
Section: Pathogenenic Mechanismsmentioning
confidence: 99%